Abnormal response to chronic social defeat stress and fear extinction in a mouse model of Lynx2-based cholinergic dysregulation - Anderson, Kristin R.; Rogu, Peter J.; Palumbo, Talulla B.; Miwa, Julie M. (Frontiers in Neuroscience, 2025)
Nicotinic receptor signaling is influential in modulating appropriate responses to salient stimuli within a complex environment. The cholinergic neurotransmitter system drives attention to salient stimuli such as stressors, and aids in orchestrating the proper neural and behavioral responses. Dysregulation of this system, however, has been implicated in altered anxiety regulation and mood disorders. Among the multiple layers of regulation are protein modulators such as Lynx2/Lypd1, which provides negative nicotinic acetylcholine receptor regulation within anxiety-related circuits, such as the amygdala and medial prefrontal cortex, among other brain regions. Mice null for Lynx2/Lypd1 (Lynx2 KO) show elevated basal anxiety-like behavior in tests such as elevated plus maze, light-dark box and social interaction assays. Here, we queried how a line predisposed to basal anxiety-like behavior would respond to specific stressors, using validated models of experiential-based affective disorders such as fear extinction, acute and chronic social defeat stress assays. We discovered that Lynx2 KO mice demonstrate an inability to extinguish learned fear during fear extinction tests even during milder stress conditions. In social defeat studies, contrary to our predictions, the Lynx2 KO mice switched from a socially avoidant phenotype (which could be considered susceptible) before defeat to a social approach/resilient phenotype after defeat. Consistent with reports of the inverse relationship between resilience and BDNF levels, we observed reduced BDNF levels in the VTA of Lynx2 KO mice. Furthermore, we provide evidence for the functional role of α7 nicotinic receptor subtypes by phenotypic rescue of fear extinction and social defeat phenotypes by MLA antagonism of α7 nicotinic acetylcholine receptors, or by crossing with α7 nicotinic acetylcholine receptor null mutant mice. A stable physical interaction between LYNX2 and α7 nAChRs was observed by co-immunoprecipitation of complexes from mouse amygdalae extracts. Together, these data indicate that responses to specific stressors can become aberrant when baseline genetic factors predispose animals to anxiety dysregulation. These studies underscore the critical nature of well-regulated nicotinic receptor function in the adaptive response to environmental stressors.